Clinical utility of calprotectin and lactoferrin in patients with inflammatory bowel disease: is there something new from the literature?. (August 2012) - Caccaro, Roberta; D'Incà, Renata; Pathak, Surajit; Sturniolo, Giacomo Carlo
The identification of noninvasive biomarkers is still one of the major issue for gastroenterologists dealing with inflammatory bowel disease patients, due to the chronicity of these conditions and the early onset of symptoms in the majority of cases. Research attention has focused mainly on fecal proteins, especially calprotectin and lactoferrin, and most of the published data are reassuring about their applicability in the diagnosis and monitoring of these patients. However, there are still pending questions regarding the reliability of fecal proteins especially in the era of mucosal healing and biologics.